Tsunami risk awareness, hazard warning knowledge, and intended evacuation behavior among beach users in Bantul, Indonesia - Amri, Ikhwan; Giyarsih, Sri Rum; Ruslanjari, Dina (International journal of disaster risk reduction, 2024)
Tsunamis, although less frequent than other coastal hazards, are indispensable in tourism disaster management. Hence, enhancing preparedness is crucial for minimizing disaster risks for both coastal communities and visitors. This research delves into the preparedness of beach users in anticipating tsunami hazards in the coastal regions of Bantul, Yogyakarta Special Region (DIY) Province, Indonesia. Through questionnaire interviews involving 221 participants, the study evaluated risk awareness, knowledge of hazard warnings, and intended evacuation behaviors. Survey results revealed that the majority of beach users recognized the tsunami hazard in the coastal destinations they visited. A key challenge related to tsunami warning knowledge was the prevalent belief that tsunamigenic earthquakes always coincided with strong tremors, and many were unfamiliar with early warning systems. In terms of intended evacuation behaviors, most beach users accurately considered earthquakes as the basis for their self-rescue response time. The prevailing choice for evacuation was running inland for direction and on foot for the mode, while the average understanding of evacuation routes was moderate. The preparedness levels of beach users differed depending on their origin, with those from outside the DIY Province generally having the lowest understanding of particular tsunami warning indicators and evacuation routes. This study recommends an expansion of risk communication strategies and the reinforcement of proactive planning to ensure optimal protection for individuals in coastal destinations.